Evaluating the Efficiency and Reliability of Fertilizer Subsidy Systems: The Role of Blockchain in Driving Enhancements in Tanzania - O. D. Mbita; M. R. Nicholaus; R. K. Twahir (Journal of Applied Sciences and Environmental Management)
This paper aims to evaluate the efficiency and reliability of fertilizer subsidy systems in the Mbeya Region of Tanzania, while exploring the role of blockchain technology in driving enhancements to these systems. The research presents a blockchain-based e-voucher system as the innovative solution to these challenges, providing a robust framework that incorporates architectural design and algorithmic solutions to enhance efficiency within the distribution process. The findings demonstrate significant improvements in addressing the identified challenges, including streamlined application processing, voucher issuance and redemption, reimbursement procedures, and increased transparency and traceability. The proposed hybrid architecture integrates well-structured algorithms to improve operational efficiency and ensure a more secure and fair distribution system. These findings underscore the urgent need for novel approaches to improve agricultural productivity and food security, advocating for the widespread adoption of blockchain technology within the agricultural sector.